دور الرقابة المالية الخارجية في تجسيد مفهوم حوكمة الشركات (الرقابة عن طريق مندوب الحسابات في الجزائر نموذجا) - بلجراف, سامية (Revue jurisprudence, 2020)
يتجسد مفهوم حوكمة الشركة من خلال تحديد مجموعة الضوابط التي تحدد مسؤوليات وواجبات أعضاء الإدارة  داخل الشركة بما يحقق حماية فعالة لحقوق أصحاب المصالح فيها من خلال وضع آلية تحقيق التوازن بين الأهداف الاقتصادية والاجتماعية للشركة من جهة وبين أهداف المساهمين الفردية والجماعية من جهة أخرى، ورغم كفاية قواعد الحوكمة لضمان فعالية مجلس الإدارة إلا أن وجود آليات للرقابة الداخلية عن طريق الجمعيات العامة والرقابة الخارجية تعتبر من أهم متطلبات الحوكمة ومحاورها الرئيسية، ويعتبر مندوب الحسابات صورة من صور الرقابة باعتباره مراجع مؤهل وحيادي للتحقق من صحة المعلومات وكافة البيانات المحاسبية الأخرى وممارسة مهنتهم بكل استقلالية ونزاهة.  . الكلمات المفتاحية: حوكمة الشركات، الرقابة الخارجية على الشركات، مندوب الحسابات.   Abstract: The concept of corporate governance through a set of controls that define the responsibilities and the duties of the members of the administration within the company to achieve an effective protection of the stakeholders ‘rights through the development of a mechanism to achieve a balance between the economic and social objectives of the company, on the one hand, and the objectives of the collective and individual shareholders on the other hand. And despite the adequacy of the rules of governance to ensure the effectiveness of the board of directors, it happens that the presence of internal control mechanisms through general assemblies and external oversight mechanisms are considered as one of the most important requirements for governance and its main axis. The representative of the accounts is considered as a form of censorship as qualified and impartial auditor to verify the information and all other accounting data, he exercises his profession with a complete independence and integrity. Key words: Corporate governance- the external control to the company- The representative of the accounts .